Cutaneous vascular and sweating responses to intradermal administration of ATP: a role for nitric oxide synthase and cyclooxygenase?. (17th April 2015) - Fujii, Naoto; McGinn, Ryan; Halili, Lyra; Singh, Maya Sarah; Kondo, Narihiko; Kenny, Glen P.
Abstract : Key points: In humans in vivo, the mechanisms behind ATP‐mediated cutaneous vasodilatation along with whether and how ATP increases sweating remains uncertain. Recent work has implicated nitric oxide synthase (NOS), cyclooxygenase (COX) and/or adenosine in the modulation of cutaneous vasodilatation and sweat production during both local (i.e. localized heating) and whole‐body heat stress (i.e. exercise‐induced heat stress). We evaluated whether ATP‐mediated cutaneous vasodilatation and sweating is mediated via NOS, COX and/or adenosine. We show that in humans in vivo, intradermal administration of ATP induces pronounced vasodilatation which is partially mediated by NOS, but neither COX nor adenosine influences ATP‐mediated vasodilatation, and ATP alone does not induce an increase in sweating. These findings advance our basic physiological knowledge regarding control of skin blood flow and sweating, and provide insight into the mechanisms governing thermoeffector activity, which has major implications for whole‐body heat exchange and therefore core temperature regulation in humans during heat stress. Abstract: In humans in vivo, the mechanisms behind ATP‐mediated cutaneous vasodilatation and whether and how ATP increases sweating remain uncertain. We evaluated whether ATP‐mediated cutaneous vasodilatation and sweating is mediated via nitric oxide synthase (NOS), cyclooxygenase (COX) and/or adenosine‐dependent mechanisms. Cutaneous vascular conductance (CVC, laser Doppler perfusion units/mean arterial pressure) and sweat rate (ventilated capsule) were evaluated at intradermal microdialysis forearm skin sites, each receiving pharmacological agents (two separate protocols). In Protocol 1 ( n = 12), sites were perfused with: (1) lactated Ringer solution (Control), (2) 10 mm N ω ‐nitro‐l ‐arginine (l ‐NNA, a NOS inhibitor), (3) 10 mm ketorolac (Ketorolac, a COX inhibitor) or (4) a combination of 10 mm l ‐NNA + 10 mm ketorolac (l ‐NNA + Ketorolac). In Protocol 2 ( n = 8), sites were perfused with: (1) lactated Ringer solution (Control) or (2) 4 mm theophylline (Theophylline, an adenosine receptor inhibitor). At all sites, ATP was simultaneously perfused at 0.12, 1.2, 12, 120 and 1200 nm min −1 (each for 20 min). Relative to CVC at the Control site with ATP infused at 120 nm min −1 (71 ± 9% of max CVC), CVC at the Ketorolac site was comparable (64 ± 13% of max CVC, P = 0.407), but lower atl ‐NNA (51 ± 15% of max CVC, P = 0.040) andl ‐NNA + Ketorolac (51 ± 13% of max CVC, P = 0.049) sites. Conversely, across the four skin sites at any other ATP infusion rate (all P > 0.174), no differences in CVC were observed. Theophylline did not influence CVC at any ATP infusion rate (all P > 0.234). Furthermore, no ATP infusion rate elicited an increase in sweating from baseline at any skin site (all P > 0.235). We show that NOS, but neither COX nor adenosine receptors, modulates ATP‐mediated cutaneous vasodilatation, whereas ATP does not directly increase sweating.